Packaging storage study and accelerated shelf life testing of banaba tea - Loverio, Jennifer P.; Dumelod, Benelyn Domingo (1997.)
The sorption isotherm of banaba tea showed that it is stable at water activity values of 0.10 to 0.80. At water activity exceeding 0.80, however, there was an increase in the hygroscopicity of the product making it susceptible to microbial activity. The computed monolayer of banaba tea is 3.24 which is equivalent to water activity value of 0.17 or to RH value 17%. The storage study revealed that the packaging material PET/Al/PE and CPP/VMOPP can withstand temperature extremes without apparent seal and package failure. Both packaging materials provided excellent moisture protection to the product, thus keeping moisture absorption low at temperatures 0 and 37°C. The estimated shelf life of the product, using the Half Value Period (HVP) method is 196,458.41 days, 45,832.80 and 3590.91 for PET/Al/PE, CPP/VMOPP and PP, respectively. Using ASLT for banaba tea, the reaction kinetics of its microbial properties were compared with each other. PET/Al/PE had the largest k value of the three packaging materials followed by CPP/VMOPP then PP. The increase in the microbial count of banaba tea follows the first order reaction. The reaction rate constant (k) of the samples increased with increasing temperature. Through extrapolation, the shelf life of the product in PET/Al/PE at 30°C was determined to be 20.45 days while those stored in CPP/VMOPP and PP were 20.67 and 10.35 days respectively, assuming that the microbial count at the end of the shelf life is 10^4 cfu/g banaba tea.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Tea -- Philippines; Banaba tea